Analysis of Demographic Factors on Perceptions of Inventory Managers towards Healthcare Performance - Rashid, Aamir; Amirah, Noor Aina; Yusof, Yusnita; Mohd, Adnan Tawfiq (The Economics and Finance Letters, 2020)
The healthcare sector has proven as one of the most crucial sectors, especially during a situation like COVID-19 pandemic. Further, healthcare is an area of concern that significantly influences economic growth. Higher rates of mortalities have contributed to the issue of whether inventory managers are paying adequate attention to the ongoing pharmacy and other inventory-related operations in striving for productivity optimization. This paper aimed to determine whether there is a substantial difference between individual factors regarding the perceptions of inventory managers on healthcare performance. This research applied the quantitative method through IBM-SPSS statistics, and 200 inventory managers employed at different public healthcare facilities of Punjab, Pakistan were randomly selected for the research survey. The research found that any difference in the attributes of demography does not affect the perceptions of inventory managers towards healthcare performance and is equally essential regardless of their demographic attributes. This research is useful to the department of health, to the body of knowledge, public and private healthcare facilities. Further research could examine the mediation of demographic attributes in back-log inventories and healthcare performance.